Корневые функционалы на 1-мерном многообразии - Сейфуллин, Т.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
For a system of (n–1) polynomials in n variables, we consider a bilinear operation of generation of root functionals which allows one to obtain the third root functional from two root functionals.